PENGARUH ARAH KEWIRAUSAHAAN DAN BUDAYA INSTITUSI TERHADAP KAPABILITAS MANAJEMEN SERTA DAMPAKNYA PADA KINERJA PERUSAHAAN DI PT. MEBEL MEDAN - Siti Normi (Universitas Methodist Indonesia, 2018)
The purpose of this research is to analyze Entrepreneurship Orientation as well as Organization Culture's influence on management skills and also their impact on PT. MEBEL MEDAN performance simultaneously and partially. There were 105 employees in PT. MEBEL MEDAN which become the sample of this research. The method of analysis used in this experiment are Pearson Correlation and Path Analysis. The result of this research stated that Entrepreneurship Orientation directly affect management skills partially, however it does not affect directly on the employee performance. Organization Culture does not affect directly on management skills partially, but Organization Culture directly affect the company performance. Management skills have direct impact partially against company performance. Entrepreneurship Orientation, Organization Institution, and also Management skills have direct impact simultaneously on organizational performance.